The impact on new-onset stress and PTSD in relatives of critically ill patients explored by diaries study (The "INSPIRED" study). Issue 6 (November 2018) - Schoeman, Tom; Sundararajan, Krishnaswamy; Micik, Svatka; Sarada, Pooja; Edwards, Suzanne; Poole, Alexis; Chapman, Marianne
Abstract: Background: There is rising prevalence of post-traumatic-stress-disorder (PTSD) in patients and their relatives after ICU discharge. The impact of ICU diaries on PTSD in relatives of critically ill patients in Australia has not been fully evaluated. Objectives: To determine if relatives of an Australian critically ill population were interested in using ICU diaries. To determine the prevalence and impact of ICU diaries upon symptoms of PTSD, depression and anxiety in relatives of an Australian critically ill population. Methods design: Prospective, observational, exploratory study. Setting: Royal Adelaide Hospital (RAH), Adelaide, Australia. Participants: One hundred and eight consecutive patients, staying >48 h in a level 3 ICU were identified. A survey using DASS-21, IES-R questionnaires was performed on admission followed by a repeat survey 90 days post discharge from ICU. An IES-R score >33 was used to define severe PTSD symptoms. A comparison between subjects who did and did not complete their diaries was performed. Results: Forty subjects refused to participate, eight were excluded, and sixty family members were included for analysis, thirty-six of whom completed diaries. There was no statistically significant difference between PTSD symptom scores at follow-up controlling for useful diary completion (complete – see methods) and PTSD at baseline. There was a statistically significant association between PTSD and unemployment, controlling for PTSD at baseline (P value = 0.0045). Family members had significantly higher odds of PTSD at baseline compared to 3 month follow up (P value = 0.0092, Odds Ratio = 3.3, 95% CI: 1.3, 8.2). This was independent of the completeness of the diaries and adjusted for clustering on subject. Family members with incomplete diaries were less likely to report depressive symptoms at baseline (P value = 0.0218, estimate = −4.6, 95% CI: −8.5, −0.7). Diary completion was not indicative of the likelihood of family members to report PTSD symptoms (P value = 0.5468, estimate = −1.6, 95% CI: −6.8, 3.6). Conclusion: ICU diaries were often not completed and completion did not appear to be related to the incidence of stress, anxiety, depression and PTSD symptoms in the families of patients in the ICU. This may be because Australian families are generally not interested in maintaining a diary.